Magnitude of Multidrug Resistance and Associated Factors of Pulmonary Tuberculosis Among Adult Smear Positive Patients in Eastern Ethiopia - Amin Z; Mitiku H; Marami D; Shume T; Weldegebreal F (Infection and Drug Resistance, 2021)
Ziad Amin,1 Habtamu Mitiku,2 Dadi Marami,2 Tadesse Shume,2 Fitsum Weldegebreal2 1Harari Health Research and Regional Laboratory, Harar, Ethiopia; 2Department of Medical Laboratory Sciences, College of Health and Medical Science, Haramaya University, Harar, EthiopiaCorrespondence: Fitsum Weldegebreal Email fwmlab2000@gmail.comBackground: In Ethiopia, multidrug resistant tuberculosis is a major public health problem. However, information is scarce regarding MDR-TB and associated factors.&#x00A0Objective: The study was aimed to assess the magnitude of multidrug resistance and associated factors of pulmonary tuberculosis among adult smear-positive patients in Harari regional state health facilities, eastern Ethiopia.Methods: A cross-sectional study was conducted among 395 adult smear-positive pulmonary tuberculosis patients attending health facilities from March to October 2019. Smear-positive sputum samples were collected from health facilities, and transported to Harari Health Research and Regional Laboratory, and tested for drug susceptibility using a line probe assay. Data were analyzed using Statistical Package for Social Sciences version 20. Bivariate and multivariable logistic regression analyses with 95% confidence intervals were carried out to identify factors associated with multidrug-resistant tuberculosis.Results: The overall magnitude of multidrug-resistant tuberculosis was 3.8% (15/395) (95% CI: 2.0– 5.8%). Being male (AOR = 4.9; 95% CI: 1.16, 20.5), patients with a previous history of tuberculosis (AOR = 4.9; 95% CI: 1.5, 29.6), treatment failure (AOR = 8.5; 95% CI: 1.61, 45.3), treatment default (AOR = 10.38; 95% CI: 1.86, 58.0), human immunodeficiency virus co-infection (AOR = 9.83.95% CI: 3, 21, 30.1) and a previous history of contact with multidrug-resistant tuberculosis patients (AOR = 14.4; 95% CI: 3.1, 67.6) had higher odds of multidrug-resistant tuberculosis.Conclusion: The overall magnitude of multidrug-resistant tuberculosis was high. Strengthening the tuberculosis control program by giving special attention to HIV co-infected patients,  treatment failure and default, previously infected patients as well as to those individuals who have a history of contact with multidrug-resistant tuberculosis infected patients .Keywords: magnitude, multidrug resistance, pulmonary tuberculosis, eastern Ethiopia